Correlation Between Congenital Hypothyroidism and Hearing Loss in Newborn - Poonual, Watcharapol (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: Congenital hypothyroidism increases the risk of hearing loss which caused delay speech and language development, social and emotional problems, and educational failure. Currently, a universal hearing screening program in newborns has been implemented in Thailand. The congenital hypothyroidism is not considered as a risk factor for hearing loss resulting in restricted hospitals that do not be screening hearing loss among congenital hypothyroidism. Then this research is to study the correlation between congenital hypo-thyroidism and hearing loss in a newborn in Uttaradit hospital, Thailand. Methods: A retrospective cohort study of 382 newborns in Uttaradit hospital between January 2011 to June 2020 was obtained from medical records, Thyroid-stimulating hormone (TSH) screening report in newborn, the evaluation of otoacoustic emission (OAE) and auditory brainstem response (ABR), divided into 2 groups, 62 patients were congenital hypothyroidism (exposed group) and 320 patients were non-congenital hypothyroidism (non-exposed group). Data were analyzed by using descriptive statistics and analytical statistics by a computer program. Results: Newborn with congenital hypothyroidism was 2.5 times significantly greater risk of hearing loss (95% CI 1.27 - 4.95, P = .008). Conclusions: Congenital hypothyroidism affected hearing loss in newborns. Therefore, early screening should be necessary for newborns to reduce the risk of hearing loss and also improve the quality of life